Alvimopan as part of the Enhanced Recovery After Surgery protocol following radical cystectomy is associated with decreased hospital stay. (26th March 2021) - Hanna, Peter; Regmi, Subodh; Kalapara, Arveen; Mulpuri, Kalyana Srujana; Zabell, Joseph; Albersheim, Jacob; Wahr, Joyce; Randle, Darrel; Kaizer, Alexander; Patten, Luke; Konety, Badrinath; Weight, Christopher
Abstract : Objective: To study the effect of alvimopan and the Enhanced Recovery After Surgery protocol on length of hospital stay in patients undergoing radical cystectomy. Methods: Our retrospective study involved 296 consecutive patients undergoing radical cystectomy for bladder cancer at our institution from 2010 through 2018. Patients were grouped according to three stages of the Enhanced Recovery After Surgery protocol implementation: (i) pre‐Enhanced Recovery After Surgery (group A; n = 146); (ii) pre‐alvimopan Enhanced Recovery After Surgery (group B; n = 102); and (iii) Enhanced Recovery After Surgery plus alvimopan (group C; n = 48). The primary outcome was the length of hospital stay. Secondary outcomes were time to first bowel movement, time to tolerate a regular diet, the incidence of postoperative ileus, postoperative complications and 30‐day readmission rate. Results: Group C showed a significantly shorter median length of hospital stay (7 days, P = 0.003), shorter gastrointestinal recovery time (4 days, P = 0.018) and a lower rate of postoperative ileus (14.6%, P = 0.005). The reduction in length of hospital stay, gastrointestinal recovery time and a lower rate of postoperative ileus was significant after controlling for other confounders on multivariable regression analysis. With the open approach, group C showed a significantly shorter length of hospital stay and gastrointestinal recovery time ( P = 0.005, P = 0.001, respectively); however, in robotic cohorts, no significant differences were observed. There was no difference among groups in the 30‐day readmission rate or postoperative complications. Conclusions: Patients undergoing radical cystectomy and managed by an Enhanced Recovery After Surgery protocol experience a significantly shorter length of hospital stay when receiving alvimopan as part of the protocol. Patients seem to derive the optimum benefits of alvimopan when it is used with an open approach; however, these benefits become less obvious with the robotic approach.